2020
DOI: 10.3390/ma13122679
|View full text |Cite
|
Sign up to set email alerts
|

Profile Features of Emulsified Asphalt Mixture Containing Steel Slag Based on Laser Scanning

Abstract: Micro-surfacing (MS), made of emulsified asphalt, is the most commonly used preventive maintenance technology in asphalt pavement. However, the studies on profile features of MS based on aggregate morphology are few. This study evaluated the profile features of MS and its effect on skid resistance. The aggregate morphologies were first characterized and modified emulsified asphalt was prepared. The three-dimensional profile features of four kinds of MS samples were captured by laser texture scanner. Results il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Ames Engineering has developed a laser scanner SLP, which uses the principle of laser triangulation reflection to obtain the function of the fluctuation amplitude of the measured pavement surface changing with the moving distance. Wang et al [24] developed a laser texture device to test the profile of different micro surfacing pavements and indicated that the use of steel slag can benefit the skid resistance of pavement. However, considering the current measurement and evaluation of asphalt pavement texture, the low scanning accuracy limited to the scale of macro pavement texture still exists.…”
Section: Introductionmentioning
confidence: 99%
“…Ames Engineering has developed a laser scanner SLP, which uses the principle of laser triangulation reflection to obtain the function of the fluctuation amplitude of the measured pavement surface changing with the moving distance. Wang et al [24] developed a laser texture device to test the profile of different micro surfacing pavements and indicated that the use of steel slag can benefit the skid resistance of pavement. However, considering the current measurement and evaluation of asphalt pavement texture, the low scanning accuracy limited to the scale of macro pavement texture still exists.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many researchers are focusing on this topic, and construction and building materials have been considered as the best way to reuse such an enormous amount of industry silicate solid wastes [ 1 ]. For instance, steel slag has been successfully used in pavement engineering [ 2 , 3 , 4 ], fly ash is widely reused as cementitious materials in concrete [ 5 , 6 , 7 ], and waste tire rubber can be reused to improve the rutting resistance of asphalt pavement [ 8 , 9 , 10 ]. Along with these developments, there are still many challenges that should be further discussed.…”
mentioning
confidence: 99%
“…Steel slag, a by-product from the steel-making industry treated as a typical solid waste, was reused in pavement engineering as aggregate. Feng used steel slag for pavement micro-surfacing and characterized its surface profile by laser scanning [ 3 ]. They found that steel slag can improve the skid resistance of pavement micro-surfacing due to its advantages of excellent polish resistance.…”
mentioning
confidence: 99%